Optimization and kinetic study of biodiesel production through esterification of oleic acid applying ionic liquids as catalysts - Roman, Fernanda (2018)
In this study, 1-methylimidazolium hydrogen sulfate, [HMIM]HSO4, ionic liquid, was successfully applied as a catalyst in the biodiesel production through the esterification reaction of oleicacid withmethanol.A response surface methodology (RSM) known as Box-Behnken Design (BBD) was applied to optimize the main experimental reaction conditions,using a set of 27 experiments.This optimization was based on the maximization of both the conversion of oleic acid and the Fatty Acid Methyl Esters (FAME) content of the obtained biodiesel samples.It was concluded that the two most relevant parameters for both the conversionand the FAME content were the molar ratio between oleic acid and methanol and the catalyst dosage.Accordingly to the model,the optimum condition for the maximum conversion was determined as being 8h, 110 ± 2°C, 15:1M ratio methanol/oleic acid and a catalyst dosage of 15wt%,resulting in a 95% conversion and for the maximum FAME content were 8h,110 ± 2°C,14:1M ratio and a catalyst dosage of 14wt%,leading to a FAME content of 90%. The kinetics of the esterification reaction was also evaluated,and the experimental results were well described using a third-order reaction model. The kinetic parameters were experimentally determined,and the value of the activation energy was 6.8kJ/mol and the pre-exponential factor was 0.0765L2.mol−2.min−1 confirming that the ionic liquid,[HMIM]HSO4,is a good alternative for replacing traditional catalysts for biodiesel production through esterification reaction.